Early Effects of Liver Regeneration on Endocrine Pancreas: In Vivo Change in Islet Morphology and In Vitro Assessment of Systemic Effects on β-Cell Function and Viability in the Rat Model of Two-Thirds Hepatectomy - Moreau, F.; Seyfritz, E.; Toti, F.; Sigrist, S.; Bietigier, W.; Pinget, M.; Kessler, L. (Hormone and Metabolic Research, 2014)
Liver and pancreas share key roles in glucose homeostasis. Liver regeneration is associated with systemic modifications and depends especially on pancreatic hormones. The aim of the study was to investigate the role of systemic factors released after two-thirds hepatectomy (2/3H) on early possible consequences of liver regeneration on endocrine pancreas structure and function. The pancreas and serum were harvested 1, 2, or 3 days after 2/3H or sham operation in Lewis rats. The HGF and VEGF serum concentrations and plasma microparticles levels were measured. The fate of endocrine pancreas was examined through islets histomorphometry and function in sham and 2/3H rats. β-Cell line RIN-m5F viability was assessed after 24 h of growth in media supplemented with 10% serum from 2/3H or sham rats instead of FCS. Three days after surgery, the pancreas was heavier in 2/3H compared to sham rats (0.56 vs. 0.40% of body weight, p<0.05) and the proportion of islets of intermediate size was lower in 2/3H rats (5 vs. 15%, p<0.05). Compared to Sham, sera obtained 3 days after hepatectomy were more efficient to maintain the viability of RIN-m5F cells (99 vs. 67%, p<0.01). Three days after surgery, no significant differences in serum HGF, a trend to significant increase in VEGF concentration and a significant increase in microparticles levels, were observed in 2/3H vs. sham rats (9.8 vs. 6.5 nM Phtd Ser Eq., p<0.05). Liver regeneration is associated with early effects on islets and could influence β-cell viability and function by systemic effect.
Keywords: liver regeneration; β-cells; systemic factors